2011
DOI: 10.1073/pnas.1103341108
|View full text |Cite
|
Sign up to set email alerts
|

Clone history shapes Populus drought responses

Abstract: Just as animal monozygotic twins can experience different environmental conditions by being reared apart, individual genetically identical trees of the genus Populus can also be exposed to contrasting environmental conditions by being grown in different locations. As such, clonally propagated Populus trees provide an opportunity to interrogate the impact of individual environmental history on current response to environmental stimuli. To test the hypothesis that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
129
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 163 publications
(146 citation statements)
references
References 40 publications
(33 reference statements)
7
129
2
Order By: Relevance
“…This would require epialleles to be stably inherited across one or two generations, depending upon whether the signal is a result of the exposure of the native open-pollinated tree (grandparent of our seed lots) or the seeds developing on these trees, respectively. In addition, the intrageneration memory would also need to persist over more than 18 years and across six opportunities for maternal epigenetic reset (Tal et al 2010;Raj et al 2011). These reset opportunities include growth of the parental genotypes in (i) different seedling nurseries in Western Australia, (ii) different base population field trials in Western Australia for 5-6 years (Costa e Silva et al 2006), (iii) grafting of scions and subsequent nursery growth (c. 1 year), (iv) planting in an arboretum in Western Australia (2-4 years), (v) re-grafting and nursery growth in Tasmania (7-12 months) and (vi) planting in Tasmania in the common environment seed orchard studied (5-6 years) .…”
Section: Discussionmentioning
confidence: 99%
“…This would require epialleles to be stably inherited across one or two generations, depending upon whether the signal is a result of the exposure of the native open-pollinated tree (grandparent of our seed lots) or the seeds developing on these trees, respectively. In addition, the intrageneration memory would also need to persist over more than 18 years and across six opportunities for maternal epigenetic reset (Tal et al 2010;Raj et al 2011). These reset opportunities include growth of the parental genotypes in (i) different seedling nurseries in Western Australia, (ii) different base population field trials in Western Australia for 5-6 years (Costa e Silva et al 2006), (iii) grafting of scions and subsequent nursery growth (c. 1 year), (iv) planting in an arboretum in Western Australia (2-4 years), (v) re-grafting and nursery growth in Tasmania (7-12 months) and (vi) planting in Tasmania in the common environment seed orchard studied (5-6 years) .…”
Section: Discussionmentioning
confidence: 99%
“…In poplar cuttings of the same genotype obtained from different geographic locations, subsequently grown under common environmental conditions, and exposed to drought stress, Raj et al (2011) observed differences in genome-wide DNA methylation levels and transcriptome composition related to climate conditions, in which parental trees were growing. Genotypic variation for both DNA methylation and yield-related traits and a relationship between them was observed in Euramerican black poplar hybrids (Gourcilleau et al 2010).…”
Section: Hitherto Knowledge Of Epigenetic Variation In Treesmentioning
confidence: 99%
“…To find support for this hypothesis, we examined published Populus leaf microarray data sets derived from oxidative stress experiments. The analysis encompassed 48 paired comparisons (stressed versus unstressed samples) of drought (Wilkins et al, 2009;Cohen et al, 2010;Hamanishi et al, 2010;Raj et al, 2011;Chen et al, 2013), wounding (Yuan et al, 2009), pathogen (Azaiez et al, 2009), and ozone responses (Street et al, 2011). After quality control filtering, DE of the 144 driver genes, when present, was assessed by fold change and P values (see Methods) and shown in box-and-whisker plots for all (A) Scatterplot of differential expression and differential connectivity between the wild-type (WT) and FD-Irp9 subnetworks.…”
Section: Potential Drivers Of the Sa-modulated Networkmentioning
confidence: 99%